Understanding The Structural Tissue of Pectoral Finless Albino African Catfish Clarias gariepinus Originating From Pond Cultivation - Farikhah; Aminin; Trisna Rama Dani; Ami Maghfironi (Jurnal Biodjati, 2025)
The loss of pectoral fin is an undesirable trait always found in almost all catfish breeding programmes in Indonesia, so further investigation is needed to clarify this problem. This study aims to describe albinism in fish with pectoral fin deformity from an immunohistochemical perspective by evaluating the correlation between two proteins (TBX5 protein and TYR protein) from eye and skin tissues. We used an individual albino fish (TL = 42 cm) found by local farmers in the Kebomas district, Gresik, to study the histological differences between albino fish without pectoral fins and black fish with regular pectoral fins using descriptive methods. The histotechniques using HE staining followed the Bioscience Laboratory, and the immunohistochemical staining was performed according to the Biomedical Laboratory procedure at Brawijaya University. The slides were scanned using Aperio Scanning CS2. Morphological structure differences determination used a t-test (α = 0.05). Spearman's rank correlation assessed the relationship between fin morphology and albinism. The results showed significant differences between the skin and retinal thickness of the two fish (p <0.05), and the total retinal thickness of albino fish without pectoral fins was significantly thinner than that of regular fish. Rank correlations showed a positive association between pectoral fin loss and reduced skin and eye histology. The histochemical studies indicated that TBX5 is an important factor in pigmentation and fin development, but additional factors may disrupt TYR regulation in albino fish. The results of this study provide further evidence for considering pectoral fin phenotype as one of the evaluation factors to make the success of a breeding program.